A preliminary investigation into self-compassion and compassion-based intervention for mental health in the performing arts - Courtney C. Walton; James N. Kirby; Sabrina McKenzie; Sabrina McKenzie; Caroline X. Gao; Caroline X. Gao; Rosemary Purcell; Rosemary Purcell; Simon M. Rice; Simon M. Rice; Margaret S. Osborne; Margaret S. Osborne (Frontiers in Psychology)
ObjectivesVery little is known about the role of self-compassion on performing artists’ mental health. This project had two primary aims. First, was to examine the relationship between self-compassion and mental health among performing artists in dance, music, and acting. Second, was to test a brief compassion-based intervention to establish proof of concept for future work.MethodTwo sequential studies recruiting Australian performing artists were conducted. In Study 1, a cross-sectional online survey of performing artists explored patterns of association between self-compassion and mental health. In Study 2, participants engaged with a brief compassion-based intervention including an online workshop and daily meditation over 3 weeks. Descriptive pre-post data combined with thematic analysis of semi-structured interview transcripts identified performer perspectives of the compassion-based intervention.ResultsIn Study 1, 211 participants were included in the final cross-sectional analysis, which showed that the intention to be self-compassionate was associated with lower symptoms of depression and anxiety, and higher wellbeing, even while controlling for several key demographic and risk factors (stress, alcohol use, and body appreciation). In Study 2, ten participants completed the intervention with medium-large improvements in self-compassion and small improvements in wellbeing and body appreciation. Qualitative data demonstrated that participants experienced self-compassion to be helpful, however fears of lowering standards existed. Participants feedback from this study can now directly inform future compassion-based interventions among performers.ConclusionWhile acknowledging the small sample size, these findings suggest that self-compassion may help performing artists manage various forms of internal, interpersonal, and environmental distress. These findings warrant progression to controlled evaluation of compassion-based interventions within larger samples of performing artists.